Human Resource Management Strategies to Improve Teacher Performance at YPI Braja Selebah Islamic Junior High School - Martini Martini; Mispani Mispani; Dian Anggraini (CV. Bimbingan Belajar Assyfa, 2026)
The rapid shifts in the modern educational landscape have sparked growing concern about integrating moral values and academic success in Islamic elementary schools. This study aims to investigate the extent to which religious character and self-discipline serve as significant predictors of academic excellence among students in Islamic primary education. Employing a quantitative research design with a correlational approach, data were collected from a sample of students using Likert-scale questionnaires to measure character traits and standardized academic records to evaluate performance. Multiple regression analysis was used to determine the relationships among variables. The findings reveal that both religious character and self-discipline have a positive and significant impact on students' academic achievement, with self-discipline emerging as the stronger predictor. These results suggest that high levels of spiritual adherence and personal consistency foster a conducive environment for cognitive development. In conclusion, fostering moral and behavioral discipline is essential for holistic student development. Schools are encouraged to integrate character-building programs into the core curriculum to sustain long-term academic excellence.